The Urgence of Religious Education (Islam) in the Family Environment - Inayah, Anida; Haerudin, Usep Malik (Attractive : Innovative Education Journal, 2022)
This study aims to determine the meaning of religious education (Islam), knowing the purpose and urgency of religious (Islamic) education in the family environment and what are the aspects of Islamic education in the family environment. The method used is descriptive qualitative method, using the content analysis approach. The type of research used in this study is library research. The data collection in this study was taken from written sources (documentation). The data source used is using books that are relevant to the subject matter. The results of this study are that religious education is a process of gaining knowledge, understanding, and ways of behaving in accordance with Islamic teachings and values and returning to the human philosophy of religion. The Purpose of Islamic Education is a term to seek fadilah, Islamic education curriculum has a noble character and educates the human soul to behave in its life in accordance with human characteristics, namely the noble position given by Allah SWT. The family's urgency for an individual is to get his character, values, habits and emotions, and with that he changes many possibilities, abilities and willingness to become a living reality and visible behavior. For individuals, the family becomes a symbol of noble traits such as firm faith in God, sacrifice, willingness to sacrifice for the benefit of the group, love for kindness, loyalty and more, the noble value with which the family can help individuals to name it . Individuals need families from the beginning to the rest of their lives. The aspects of religious education in the family are: Islamic aqeedah education, Islamic religious education, the Principles of Islamic Teachings and Reading of the Qur'an and the Islamic education of akhlaq Islamiyah Keywords: Religious Education, Family Environment, Urgence Religious Education